2011
DOI: 10.1590/s1516-44462011000300006
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between perceived social support and severity of body dysmorphic disorder symptoms: the role of gender

Abstract: Objective: Whether social support is associated with severity of body dysmorphic symptoms is unknown. To address this gap in the literature, the present study aims to examine the association between three domains of perceived social support (i.e., family, friends, and significant others) and severity of body dysmorphic disorder symptoms. Method: Participants (N = 400) with symptoms consistent with diagnosis of body dysmorphic disorder completed measures of symptomatology and social support via the internet. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 39 publications
0
1
0
2
Order By: Relevance
“…62 Dukungan keluarga dan orang terdekat juga dapat membantu meningkatkan motivasi, kepatuhan pasien untuk tetap mengikuti terapi psikofarmaka dan non psikofarmaka, serta mengurangi gejala BDD. 67…”
Section: Tata Laksana Bdd DI Layanan Psikiatriunclassified
“…62 Dukungan keluarga dan orang terdekat juga dapat membantu meningkatkan motivasi, kepatuhan pasien untuk tetap mengikuti terapi psikofarmaka dan non psikofarmaka, serta mengurangi gejala BDD. 67…”
Section: Tata Laksana Bdd DI Layanan Psikiatriunclassified
“…The authors hypothesized that the frequency of self-reported BDD would be higher, and lower measures of self-esteem would be more common in young adults being managed for acne vulgaris compared with non-clinical community samples. As many individuals with BDD avoid mental health services and instead seek cosmetic or dermatological treatment for their perceived skin defects, dermatologists are provided with an important opportunity to intervene ( 22 ). A more rapid diagnosis is relevant, as a longer duration of symptoms is associated with more treatment-resistance and an increased risk of suicide ( 23 ).…”
mentioning
confidence: 99%
“…O Transtorno Dismórfico Corporal (TDC), é caracterizado pela grande preocupação por um defeito na aparência que interfere nas relações sociais (Marques et al, 2011). Ou seja, é um transtorno psicológico que altera a percepção da imagem corporal fazendo com que a pessoa se veja da forma diferente da realidade.…”
Section: Ressignificacões Do Corpo E Da Menteunclassified